Fatigue Following Pediatric Arterial Ischemic Stroke: Prevalence and Associated Factors. Issue 10 (28th June 2021) - Greenham, Mardee; Gordon, Anne L.; Cooper, Anna; Hearps, Stephen; Ditchfield, Michael; Coleman, Lee; Hunt, Rod W.; Mackay, Mark T.; Monagle, Paul; Anderson, Vicki
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The aims of this study were to assess the prevalence of multidimensional fatigue symptoms 5 years after pediatric arterial ischemic stroke and identify factors associated with fatigue. Methods: Thirty-one children (19 males) with pediatric arterial ischemic stroke, participating in a larger prospective, longitudinal study, were recruited to this study at 5 years poststroke. Parent- and self-rated PedsQL Multidimensional Fatigue Scale scores were compared with published normative data. Associations between parent-rated PedsQL Multidimensional Fatigue Scale, demographics, stroke characteristics, and concurrent outcomes were examined. Results: Parent-rated total, general and cognitive fatigue were significantly poorer than population norms, with more than half of all parents reporting fatigue symptoms in their children. One-third of children also reported experiencing fatigue symptoms, but their ratings did not differ significantly from normative expectations, as such, all further analyses were on parent ratings of fatigue. Older age at stroke and larger lesion size predicted greater general fatigue; older age, female sex, and higher social risk predicted more sleep/rest fatigue. No significant predictors of cognitive fatigue were identified and only older age at stroke predicted total fatigue. Greater fatigue was associated with poorer adaptive functioning, motor skills, participation, quality of life, and behavior problems but not attention. Conclusions: Fatigue is a common problem following pediatric arterial ischemic stroke and is associated with the functional difficulties often seen in this population. This study highlights the importance of long-term monitoring following pediatric arterial ischemic stroke and the need for effective interventions to treat fatigue in children.